Sapwood biomass carbon in northern boreal and temperate forests. Issue 5 (27th February 2019) - Thurner, Martin; Beer, Christian; Crowther, Thomas; Falster, Daniel; Manzoni, Stefano; Prokushkin, Anatoly; Schulze, Ernst‐Detlef
Abstract: Aim: Information on the amount of carbon stored in the living tissue of tree stems (sapwood) is crucial for carbon and water cycle applications. Here, we aim to investigate sapwood‐to‐stem proportions and differences therein between tree genera and derive a sapwood biomass map. Location: Northern Hemisphere boreal and temperate forests. Time period: 2010. Major taxa studied: Twenty‐five common tree genera. Methods: First, we develop a theoretical framework to estimate sapwood biomass for a given stem biomass by applying relationships between sapwood cross‐sectional area (CSA) and stem CSA and between stem CSA and stem biomass. These measurements are extracted from a biomass and allometry database (BAAD), an extensive literature review and our own studies. The established allometric relationships are applied to a remote sensing‐based stem biomass product in order to derive a spatially continuous sapwood biomass map. The application of new products on the distribution of stand density and tree genera facilitates the synergy of satellite and forest inventory data. Results: Sapwood‐to‐stem CSA relationships can be modelled with moderate to very high modelling efficiency for different genera. The total estimated sapwood biomass equals 12.87 ± 6.56 petagrams of carbon (PgC) in boreal (mean carbon density: 1.13 ± 0.58 kgC m −2 ) and 15.80 ± 9.10 PgC in temperate (2.03 ± 1.17 kgC m −2 ) forests. Spatial patterns of sapwood‐to‐stem biomass proportions are crucially driven by the distribution of genera (spanning from 20–30% in Larix to > 70% in Pinus and Betula forests). Main conclusions: The presented sapwood biomass map will be the basis for large‐scale estimates of plant respiration and transpiration. The enormous spatial differences in sapwood biomass proportions reveal the need to consider the functionally more important sapwood instead of the entire stem biomass in global carbon and water cycle studies. Alterations in tree species distribution, induced by forest management or climate change, can strongly affect the available sapwood biomass even if stem biomass remains unchanged.